PENEGAKAN HUKUM TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (ANALISIS PUTUSAN PENGADILAN NEGERI BATAM NOMOR 755/PID.SUS/2023/PN BTM) - Ghifary Shahab, Husein; Lumban Gaol, Selamat (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
The crime of domestic violence is any act against someone, especially women, which results in physical, sexual, psychological misery or suffering and/or domestic neglect. Domestic violence is a more physical form of action that results in injury, disability or suffering to another person. This research will discuss the regulation of the crime of domestic violence in Indonesian criminal law and the considerations of the panel of judges in the Batam District Court decision number 755/Pid.Sus/2023/Pn Btm convicting the defendant. The legal research method used is a normative juridical legal research method supported by empirical data. Using a statutory approach, conceptual approach and case approach obtained from primary, secondary and tertiary legal material sources. The regulation of the crime of domestic violence in Indonesian criminal law is regulated in the PDKRT Law and future divorce regulations are regulated in Article 404 of Law Number 1 of 2023 concerning the Criminal Code. The considerations of the Panel of Judges in Batam District Court Decision Number 755/Pid.Sus/2023/Pn Btm Sentencing the Defendant was carried out in accordance with the applicable Regulations and Legislation, especially Article 44 Paragraph (1) of the PDKRT Law. Legal facts revealed at trial where the Defendant does not find a forgiving reason that can erase his mistake or a justification that can eliminate the unlawful nature of his actions, then the Defendant must be sentenced to a crime commensurate with his mistake.